2006
DOI: 10.1270/jsbbs.56.295
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Rice (Oryza sativa L.) Genes Involved in High-Affinity Nitrate Transport during the Period of Nitrate Induction

Abstract: When breeding crops that utilize nitrogen efficiently, it is important to reveal the regulation of nitrate uptake at the molecular level. We focused on the expression of two nitrate uptake-related genes, NRT2 and NAR2, and nitrate uptake during the nitrate induction. Four rice NRT2s (OsNRT2.1~2.4) and two NAR2s (OsNAR2.1~2.2) were identified in the rice genome database. We analyzed the expression of the genes in the roots and shoots after supply of nitrate with or without ammonium pretreatment by the RT-PCR me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 57 publications
(68 reference statements)
5
69
2
Order By: Relevance
“…Using similar approaches, Pellizzaro et al (2015) revealed, for M. truncatula, a small NRT2 gene family composed of three MtNRT2 genes (named MtNRT2.1, MtNRT2.2 and MtNRT2.3), indicating a similar NRT2 family size in legume or non-legume species. Indeed, seven AtNRT2 genes were identified in A. thaliana (Orsel et al 2002a, b;Okamoto et al 2003) and four in rice (Araki and Hasegawa 2006;Cai et al 2008;Feng et al 2011). In these non-legume species, all characterized NRT2s have been reported to be strictly high-affinity nitrate transporters (Feng et al 2011;Krapp et al 2014).…”
Section: Nrt2 Familymentioning
confidence: 99%
“…Using similar approaches, Pellizzaro et al (2015) revealed, for M. truncatula, a small NRT2 gene family composed of three MtNRT2 genes (named MtNRT2.1, MtNRT2.2 and MtNRT2.3), indicating a similar NRT2 family size in legume or non-legume species. Indeed, seven AtNRT2 genes were identified in A. thaliana (Orsel et al 2002a, b;Okamoto et al 2003) and four in rice (Araki and Hasegawa 2006;Cai et al 2008;Feng et al 2011). In these non-legume species, all characterized NRT2s have been reported to be strictly high-affinity nitrate transporters (Feng et al 2011;Krapp et al 2014).…”
Section: Nrt2 Familymentioning
confidence: 99%
“…Many studies of the molecular basis of nitrate uptake reveal the existence of two gene families, namely the NRT1 and NRT2 families, which potentially encode for LATS and HATS respectively. NRT2 genes are identified in a variety of organisms including fungi, certain yeasts, green algae, and higher plants ( Unkles et al 1991;Quesada et al 1994;Trueman et al 1996;Pérez et al 1997;Quesada et al 1997;Amarasinghe et al 1998;Zhuo et al, 1999;Araki and Hasegawa 2006;Tsujimoto et al 2007). In most species, NRT2 genes are members of a multigene family: for example, seven Arabidopsis genes (AtNRT2.1-AtNRT2.7) and four rice genes (OsNRT2.1-OsNRT2.4) have been found in their genomes (Orsel et al 2002; Araki and Hasegawa 2007), and at least four NRT2 genes (HvNRT2.1-HvNRT2.4) exist in barley (Vidmar 2000a).…”
mentioning
confidence: 99%
“…In the wild-type plants, transcripts of OsNRT2.1, OsNRT2.2 and OsNRT2.4 in roots were detected starting 30 min after the beginning of nitrate treatment, suggesting that a short induction period exists in rice as reported by Araki and Hasegawa (2006). Transcripts of OsNRT2.3 were constitutively expressed.…”
Section: Expression Of Nrt2s In Roots and Shootsmentioning
confidence: 81%
“…It is of practical importance to improve the efficiency of nitrate uptake in paddy rice. As the nitrate concentration in the rhizosphere of paddy fields is estimated to be 1-10 μM (Kirk and Kronzucker 2005), in rice, NRT2 appears to play a major role in nitrate uptake (Araki and Hasegawa 2006). As in higher plants such as Arabidopsis thaliana (Orsel et al 2002) and barley (Vidmar et al 2000), rice has NRT2 family genes that are differentially regulated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation